Shared Reality Can Reduce Stressor Reactivity - Goldring, Megan R.; Pinelli, Federica; Bolger, Niall; Higgins, E. Tory (Frontiers in Psychology, 2022)
When a person faces a stressor alongside someone else, do they get more or less stressed when the other person agrees that the situation is stressful? While an equally stressed partner could plausibly amplify stress by making the situation seem more real and worthy of distress, we find that social validation during co-experienced stressors reduces reactivity. Specifically, the psychological experience of shared reality calms some people down. In Study 1, 70 undergraduate females who jointly faced a stressful event with someone else reported feeling less anxious when the other person felt the same way about the stressor, relative to when the other person appraised the situation in the opposite way or provided no indication of their appraisal. These findings were reflected in participants’ physiological reactivity, especially in the parasympathetic nervous system. In Study 2, we generalize these findings to co-experienced stressors in the daily lives of 102 heteronormative romantic couples in the New York city area. In line with tend-and-befriend theory, we found that shared reality during co-experienced stressors reduced anxiety for almost all females (99% of the sample) and for a minority of males (42% of the sample). Together, these findings unify major theories in health and social psychology by implying that shared reality reduces stressor reactivity, and that this effect is partially moderated by biological sex.